Target-guided screening of fragments (TGSOF) in the discovery of inhibitors against EV-A71 3C protease. Issue 23 (2nd March 2018) - Fu, Shengjun; Nie, Quandeng; Ma, Yuying; Song, Ping; Ren, Xuejiao; Luo, Cheng; Shang, Luqing; Yin, Zheng
Abstract : Target-guided screening of fragments (TGSOF) was developed and employed in the identification of EV-A71 3C protease (3C pro ) inhibitors. Abstract : Target-guided screening of fragments (TGSOF) was developed and employed in the identification of EV-A71 3C protease (3C pro ) inhibitors. We identified 4-acetylpyridine and 3-acetylpyridine as effective P3 fragments of an inhibitor and obtained the corresponding irreversible inhibitors12c and12f via this method. Furthermore, based on12c and12f, we have obtained reversible inhibitors17c and17f . These results demonstrated that TGSOF is a useful strategy for identifying suitable fragments in developing leads in drug discovery.